2016
DOI: 10.1039/c6cc06358f
|View full text |Cite
|
Sign up to set email alerts
|

C8–H bond activation vs. C2–H bond activation: from naphthyl amines to lactams

Abstract: Pd-catalyzed selective amine-oriented C8-H bond functionalization/N-dealkylative carbonylation of naphthyl amines has been achieved. The amine group from dealkylation is proposed to be the directing group for promoting this process. It represents a straightforward and easy method to access various biologically important benzo[cd]indol-2(1H)-one derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 80 publications
1
15
0
Order By: Relevance
“…Following the pioneering work of Miura on the Pd-catalyzed peri (C-8) arylation of naphthols with iodoarenes, 1 many other related transformations have been developed. 2 , 3 The reaction of symmetrical disubstituted alkynes with 1-naphthols in the presence of Rh(III) catalysts leads to benzo[ de ]chromenes by C–C bond formation at the peri position followed by cyclization. 4 , 5 Benzo[ de ]chromenes can also be obtained from 1-naphthols using [RuCl 2 ( p -cymene)] 2 as the catalyst.…”
mentioning
confidence: 99%
“…Following the pioneering work of Miura on the Pd-catalyzed peri (C-8) arylation of naphthols with iodoarenes, 1 many other related transformations have been developed. 2 , 3 The reaction of symmetrical disubstituted alkynes with 1-naphthols in the presence of Rh(III) catalysts leads to benzo[ de ]chromenes by C–C bond formation at the peri position followed by cyclization. 4 , 5 Benzo[ de ]chromenes can also be obtained from 1-naphthols using [RuCl 2 ( p -cymene)] 2 as the catalyst.…”
mentioning
confidence: 99%
“…[32] The previously reported carbonylative synthesis of benzo[cd]indol-2(1H)-ones was disclosed by Lei and co-workers, which involved the Pd/Cu co-catalyzed CÀ H bond activation/N-dealkylative carbonylation of naphthylamines under a carbon monoxide and oxygen (2 : 1) atmosphere. [33] The current transformation employed TFBen as an easy manipulation CO source and the picolinamide directing group could be removed during the reaction process. Mechanistic studies revealed that the N atom on the directing group was necessary and the CÀ H bond cleavage was not involved in the rate-determining step.…”
Section: Carbonylative Synthesis Of Fused-heterocycles With Tfbenmentioning
confidence: 99%
“…In 2016, Lei's group reported a palladium-catalyzed C8dealkylative carbonylation of naphthylamines 34 to synthesize methyl protected benzo[cd]indol-2(1H)-ones 35 (Scheme 18). [35] This method represents a straightforward way to access biologically active scaffolds. In order to understand the mechanism and the regioselectivity (C8 vs C2), DFT calculations were performed.…”
Section: Monodentate Directing Groupsmentioning
confidence: 99%
“…In 2016, Lei's group reported a palladium‐catalyzed C8‐dealkylative carbonylation of naphthylamines 34 to synthesize methyl protected benzo[ cd ]indol‐2(1 H )‐ones 35 (Scheme ) . This method represents a straightforward way to access biologically active scaffolds.…”
Section: C8‐functionalization Of Naphthalene Derivativesmentioning
confidence: 99%